SOSIALISASI PENGELOLAAN KEUANGAN RUMAH TANGGA DI MASA PANDEMI COVID 19 - Maya Widyana Dewi; Indra Lila Kusuma; LMS Kristiyanti (LPPM ITB AAS Indonesia Surakarta, 2021)
The socialization of household financial management during the COVID-19 pandemic in Gonilan Village, Kartasura aims to increase housewives' knowledge of household financial management in the midst of the COVID-19 pandemic, so that housewives can plan and control household finances. This service activity was held at Mrs. Warsinah's house and was attended by 15 participants consisting of housewives who entered the Gonilan area. This service activity runs smoothly according to plan. While the method used in this service activity is to conduct socialization and discussion related to household financial management material during the Covid 19 pandemic.The result of this activity is that the participants know more about managing and controlling household finances in the face of the Covid 19 pandemic. Keywords : financial management, household, covid pandemic 19